Does it really rain more often on weekends than on weekdays? - Plečko, Jaka (Acta geographica Slovenica, 2018)
The article presents the results of precipitation and aerosol (PM10) data analyses in Slovenia. Analyses of rainfall data for some areas of Slovenia, such as the Ljubljana Basin, Zasavje, Šalek Valley, Celje Basin, and the coastal area, suggest that rain on the weekend is more frequent than on weekdays; nevertheless, these deviations are not statistically significant. A comparison of three separate decades showed that the pattern of weekly rainfall in the 21st century is different than that in the last period of the 20th century. The weekly cycle of PM10 for the considered stations is quite similar to that of some of the more contaminated regions of the world. Furthermore, the connection between PM10 and precipitation in most of the analyzed cases was statistically significant.
Keywords: air pollution; onesnaženje zraka; padavine; PM10; precipitation; tedenska razporeditev padavin; weekly precipitation cycle